Direct-ink-writing (DIW) 3D printing functional composite materials based on supra-molecular interaction. (20th October 2021) - Yang, Guiyan; Sun, Youyi; Limin qin,; Li, Mengru; Ou, Kangtai; Fang, Jiang; Fu, Qiang
Abstract: Direct ink writing (DIW) is the most versatile AM technique in terms of materials development, it enables the creation of complex 3D shapes using any material by formulating a paste with controlled rheology. One of the main challenges of DIW is to design and formulate the viscoplastic and self-healing soft inks that easily flow under shear and quickly recover upon deposition. Researchers often look for flexible approaches that can be adapted to formulate printing inks with a wide range of materials. Here we report a supra-molecular interaction system composed of triethanolamine and ammonium oleate for application in DIW technology. Almost any materials (eg. rubber, plastic, ceramic, metal and composites) can be integrated into the ink system, and then can be 3D printing via shear-thinning DIW method. Furthermore, the solid contents of the ink system are higher than 80%, avoiding the formation of porous structure and dimensional changes after shaping. Present DIW method was used to construct sensors based on multi-material for application in real-time monitoring human health. This work may provide an new method to develop 3D printing materials for various practical applications. Graphical abstract: Image 1